Técnicas para avaliação in vitro do efeito de produtos fitossanitários em Bacillus thuringiensis var. kurstaki - Silva, Everton Ricardi Lozano da (2006)
The objective of this research was evaluation "in vitro" the effect of fungicides and herbicides on Bacillus thuringiensis var. kurstaki (Btk). The five fungicides: epoxiconazole, fentin hydroxide, azoxystrobin, tebuconazole and carbendazim, and five herbicides: sulfentrazone, lactofen, imazethapyr, fenoxaprop and metribuzin were tested at two concentrations, on cells and spores, in nutrient agar (NA) - solid medium (SM), and in nutrient broth (NB) - liquid medium (LM), in addition to their metabolization (MT) by Btk. For cells, the phytosanitary products in NA were tested incorporated into the medium and on filter paper disks impregnated with the products. The evaluation consisted, respectively, of the number of CFU/mL and of the formation of an inhibition halo. For cells, the Bt+products+NB mixture was incubated in Erlenmeyer flasks (30± 2°C, 150rpm, 24h)an then the NB was diluted and inoculated onto NA; the number of CFU/mL was evaluated. The MT and spore tests were performed in liquid medium (water for MT and NB for spores). The effects of the products varied with the category (fungicide and herbicide), their concentrations, technique used, contact time, and developmental stage of the pathogen. The LM test is the most indicated to evaluate the effect of the products on cells. It was observed that most fungicides were compatible with cells, and only epoxiconazole and azoxystrobin were metabolized. The herbicides, independents of the concentrations, were incompatible with cells, and only sulfentrazone and imazethapyr were metabolized. Fentin hydroxide was the only product incompatible with spore